PENERAPAN MODEL PEMBELAJARAN TEAM GAME TOURNAMENT BERBANTUAN MEDIA MONOPOLI BIOLOGI DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMA NEGARI 1 PANDAWAI - Yuskartika Bili, Eliani; Makaborang, Yohana; Loise Makatita, Audrey (Universitas Cokroaminoto Palopo, 2024)
This study aims to describe student learning outcomes before and after the implementation of the Team Game Tournament learning model with Biology Monopoly media at SMA Negeri 1 Pandawai, and to analyze the improvement in 11th-grade student performance. This research is a Classroom Action Research (CAR) with a descriptive quantitative approach, involving 36 students from class XI MIPA 2. Data were collected through observation, tests, and documentation. The results show that in the pre-cycle phase, the average cognitive score was 71.38, with 83% of students not meeting the Minimum Competency Criteria (KKM) of 78, and 17% meeting the KKM. The average affective score was 54, with 89% of students not meeting the KKM. In Cycle I, the average cognitive score increased to 80.13, with 64% of students meeting the KKM. In Cycle II, the average posttest cognitive score reached 94.16, with 94% of students meeting the KKM, and the average affective score rose to 91. The study concludes that the Team Game Tournament learning model with Biology Monopoly media effectively enhances student learning outcomes.